Industrial testing of a 3-AXIS CNC Tailor Welded Blank laser welding machine using predefined closest-distance volume interpolator - Romlay, Fadhlur Rahman Mohd
Tailor Welded Blank’s (TWB’s) technology was introduced and developed mainly for automotive industries which usually utilizing materials with different strength properties, different thicknesses, and also different surfaces coating [1]. Tailor Welded Blanks are made from individual steel sheets of different thickness, strength and coating which are joined together mostly by laser welding [2]. This manufacturing process allows for flexible part design and ensures the right material is used in the right place. Thicker or higher-strength material can be used in highly stressed areas while thinner sheets or deep drawing grades can be used in others. Expensive materials are only used where they are needed. There was some advantages drawn from the usage of this technology such as cost saving, weight reduction, and strength increment.